Life after life imprisonment - Appleton, Catherine (Clarendon studies in criminology, 2010)
Life after Life Imprisonment explores on of the most contentious and sensitive topics in criminal justice: the release and resettlement of life-sentenced offenders. This book provides an in-depth analysis of the post-prison experiences of 138 discretionary life-sentenced offernders, all of whom were released from prison across England and Wales during the mid-1990s. Using accessible and engaging data, it examines key legal developments within the criminal justice system for discretionary life-sentenced offenders, explores the frontline experiences of the criminal justice practitioners charged with the responsibility of supervising life-sentenced offenders, and analyses the 'stories' or life narratives of a group of individuals who have committed some of the most serious crimes. It also examines the process of recall for life-sentenced prisonders and explores key factors associated with failure in the community. Of interest to legal scholars and criminologists, as well as practitioners in the field, Catherine Appleton's book offers a major insight into how societies respond to serious crimes and identifies important elements of successful reintegration for released life-sentenced offenders. (Quelle: Text Verlagseinband / Verlag)